2021
DOI: 10.1016/j.yebeh.2021.108115
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and epilepsy: How are people with epilepsy in Brazil?

Abstract: During COVID-19 pandemic the global population is facing an important psychosocial distress. The aim of this study was to evaluate how people with epilepsy (PWE) in Brazil is dealing with the pandemic, in relation to seizure frequency, access to antiseizure medicines (ASM), medical follow-up, and well-being. Methods: An online questionnaire survey among PWE (group 1) and caregivers (group 2) was applied in the social networks of the Brazilian Association of Epilepsy, the official Brazilian chapter of the Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…Because of the low incidence of COVID-19 in our cohort during the first wave of the pandemic, we were unable to draw reliable conclusions on this. Fear of experiencing more severe COVID-19 disease due to epilepsy was reported by 74.5% of PWE in Brazil, while dissatisfaction with current health status was reported by 36.7%, but related to the second pandemic wave in autumn 2020 [ 32 ]. In addition, fear of belonging to an “at-risk” group may contribute to increased psychological distress during the first wave of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the low incidence of COVID-19 in our cohort during the first wave of the pandemic, we were unable to draw reliable conclusions on this. Fear of experiencing more severe COVID-19 disease due to epilepsy was reported by 74.5% of PWE in Brazil, while dissatisfaction with current health status was reported by 36.7%, but related to the second pandemic wave in autumn 2020 [ 32 ]. In addition, fear of belonging to an “at-risk” group may contribute to increased psychological distress during the first wave of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in our population there are probably more cases of COVID-19 than diagnosed. Previous studies highlighted that PWE had limited access to health services or medication during pandemic period and that no testing was performed in most PWE who reported symptoms compatible with COVID-19 [2] , [3] , [4] , [5] , [10] , [14] , [27] , [28] , [29] , making unlikely that the higher prevalence of COVID-19 in PWE was due to an easier access to health care resources of these patients during the pandemic because of their condition.…”
Section: Discussionmentioning
confidence: 99%
“…Several other aspects of the impact of the pandemic on PWE have been addressed by other researchers and were not within the scope of our study: Seizure increases during the COVID-19 pandemic have been reported independently of infections [ 7 , 22 ]. A seizure increase during the pandemic was partly explained by several problems beyond the infection itself such as dispensing of antiseizure medication (ASM), telehealth, and access to the healthcare system in general, at least in developing countries [ 9 ]. Finally, results concerning the pandemic and new-onset seizures and epilepsies were inconsistent [ 1 , 6 , 8 , 12 14 , 17 ].…”
Section: Discussionmentioning
confidence: 99%